Long-term trends of PM2.5 and its carbon content in the South Coast Air Basin: A focus on the impact of wildfires. (15th June 2021) - Enayati Ahangar, Faraz; Pakbin, Payam; Hasheminassab, Sina; Epstein, Scott A.; Li, Xiang; Polidori, Andrea; Low, Jason
Abstract: Implementation of stringent regulations on stationary and mobile sources at the local, state, and federal levels over the past two decades resulted in a substantial reduction of mass concentrations of ambient fine particulate matter (PM2.5) and its carbonaceous content including elemental carbon (EC) and organic carbon (OC) in California's South Coast Air Basin (SCAB). PM2.5, EC, and OC from sources that cannot reasonably be controlled through regulations, such as wildfires, are gaining more significance as emissions from anthropogenic sources are reduced. Among other factors, dry conditions and forest management practices in recent decades have also contributed to increased frequency and intensity of wildfire events in California, including the SCAB, and these emissions may offset expected air quality improvements due to decreases in anthropogenic emissions. We examined PM2.5 measurements to determine if wildfire emissions had impacted trends of PM2.5 and its carbonaceous fraction in the SCAB. In this work, we analyzed the long-term trends of PM2.5, EC, and OC at four sites in urban regions of the SCAB, as well as four sites in the surrounding remote areas from 2004 to 2018. The results showed that the annual concentrations were reduced across all sites with larger reductions at the urban sites compared to the remote regions. PM2.5 was reduced 31–51% in the urban and 12–35% in the remote sites. In the urban sites, EC and OC concentrations increased from 2004 to 2007 and were followed by a decline of over 50%. In the remote sites, EC peaked in 2005 with a decline afterward resulting in total reductions of 28–45%, while the OC levels were modestly reduced by 7–23%. Using a back-trajectory model combined with a fire emission inventory, we identified the days that were potentially affected by wildfires as "fire days" and compared them to the rest of the study period. The results suggest that while wildfires led to higher concentrations of PM2.5 and its carbonaceous fractions during the days impacted by fire episodes, their impacts on long-term trends or overall concentration averages were not statistically significant in the urban regions where the anthropogenic sources are dominant. However, wildfires had important impacts on PM2.5 levels in the remote sites and excluding the fire days resulted in statistically significant reductions in concentration levels. Also, OC/EC ratio was analyzed as an indicator for the contribution of wildfires and secondary organic carbon (SOC). Higher OC/EC ratios indicate larger contributions from wildfire and SOC sources compared with lower OC/EC ratios are more reflective of anthropogenic combustion emissions. While this ratio did not have an increasing or decreasing trend in the urban region, average OC/EC changed from 4.8 in 2004 to 6.9 in 2018 with a statistically significant increasing trend in the remote sites. This suggests the contribution of wildfire and secondary organic carbon sources are increasing in the remote regions of SCAB while the change in their contribution in the urban sites is statistically insignificant. Highlights: A 15-year dataset of P M 2.5, EC, and OC was analyzed for eight stations in Southern California. Significant reductions in concentration levels were observed throughout the region. The days affected by wildfire smoke were determined using back-trajectory modeling. Wildfires impacted long-term concentration trends in urban areas less than remote sites.